Near-Field Plasmonic Probe with Super Resolution and High Throughput and Signal-to-Noise Ratio - Jiang, Ruei-Han; Chen, Chi; Lin, Ding-Zheng; Chou, He-Chun; Chu, Jen-You; Yen, Ta-Jen (Nano letters, 2018)
Near-field scanning optical microscopy (NSOM) enables observation of light-matter interaction with a spatial resolution far below the diffraction limit without the need for a vacuum environment. However, modern NSOM techniques remain subject to a few fundamental restrictions. For example, concerning the aperture tip (a-tip), the throughput is extremely low, and the lateral resolution is poor; both are limited by the aperture size. Meanwhile, with regard to the scattering tip (s-tip), the signal-to-noise ratio (SNR) appears to be almost zero; consequently, one cannot directly use the measured data. In this work, we present a plasmonic tip (p-tip) developed by tailoring subwavelength annuli so as to couple internal radial illumination to surface plasmon polaritons (SPPs), resulting in an ultrastrong, superfocused spot. Our p-tip supports both a radial symmetric SPP excitation and a Fabry–Pérot resonance, and experimental results indicate an optical resolution of 10 nm, a topographic resolution of 10 nm, a throughput of 3.28%, and an outstanding SNR of up to 18.2 (nearly free of background). The demonstrated p-tip outperforms state-of-the-art NSOM tips and can be readily employed in near-field optics, nanolithography, tip-enhanced Raman spectroscopy, and other applications.